Prolene Mesh Repair of Inguinal Hernias Single Layer Vs Double Layer (Journal of Fatima Jinnah Medical University, 2018)
Objective: To compare the outcome of single layer Prolene Mesh Repair of inguinal hernias with double layer repair by Prolene Hernia System. Study Design: The was a Quasi experimental study Place and Duration of Study: Department of general surgery , Pakistan Institute of Medical Sciences from September 2006 to October 2007 Methodology: In this quasi experimental study a total 60 patients divided into two groups were enrolled, 30 in each group. All male patients diagnosed as having inguinal hernias from 18 – 80 years of age were enrolled. The study was done in six months at the Department of General Surgery, Pakistan Institute of Medical Sciences, Islamabad. Results: The average post operative pain in Group I was 5.73 and in Group II it was 6.63. The average operative time in Group I was 82.3 and in Group II it was 73.0 minutes. While the average time to return to work was 7.63 in Group I and 10.23 days in Group II. These all the study parameters, the pain score, operative time and return to work were found statistically significant when compared between both study groups (p-value =
Keywords: Prolene mesh repair, single layer, double layer, inguinal/groin hernia